The Role of Islamic Religious Higher Education in the Revitalization of Religious Moderation in Indonesia - M. Khusna Amal (Dialogia: Islamic Studies and Social Journal, 2021)
The purpose of this study is to describe the consistency of PTKI (Islamic Religious College) in fighting for religious moderation in Indonesia. This research is a literature review with a sociological-historical approach. Where through this approach, the revitalization of PTKI's religious moderation becomes a critical discourse to know. The research data is in the PTKI religious moderation movement in social and historical contexts, both in the academic corridor, curriculum, campus activism, and social roles. Data collection techniques with documentation. Researchers documented data on the PTKI movement to fight for religious moderation during the New Order and Post-Reformation eras. Data analysis used the descriptive analysis method. The study results indicate that PTKI is an Islamic institution that is consistent in fighting for the agenda of religious moderation. During the New Order period, PTKI, through campus intellectuals, pioneered the Islamic reform movement and, at the same time, made an essential contribution to the process of democratic socio-political change marked by the 1998 reform movement. In the following period (post-reform), PTKI still presents itself as an agent of moderate Islam who actively teaches, campaigns, and affirms religious moderation in its contestation with radical political Islam groups. However, PTKI's active involvement in responding to religious radicalism has contributed significantly to strengthening Indonesia's moderate Islam in the changing socio-political context.Tujuan penelitian ini guna mendeskripsikan konsistensi PTKI (Perguruan Tinggi Keagamaan Islam) dalam memperjuangkan moderasi beragama di Indonesia. Penelitian ini merupakan kajian pustaka dengan pendekatan sosiologis-historis. Di mana melalui pendekatan ini, revitalisasi moderasi beragama PTKI menjadi diskursus yang penting untuk diketahui. Data-data penelitian berupa fenomena pergerakan moderasi beragama PTKI dalam konteks sosial dan sejarah, baik dalam koridor akademik, kurikulum, aktivisme kampus, maupun peran sosial. Teknik pengumpulan data dengan dokumentasi. Peneliti melakukan dokumentasi atas data-data pergerakan PTKI dalam upaya memperjuangkan moderasi beragama pada masa Orde Baru dan Pasca Reformasi. Analisis data menggunakan metode analisis deskriptif. Hasil penelitian menunjukkan bahwa PTKI merupakan institusi Islam yang konsisten dalam memperjuangkan agenda moderasi beragama. Pada periode Orde Baru, PTKI melalui kalangan intelektual kampus, memelopori gerakan pembaruan Islam dan sekaligus berkontribusi penting dalam proses perubahan sosial-politik demokratis yang ditandai oleh gerakan reformasi 1998. Pada periode berikutnya (pasca reformasi), PTKI masih menampilkan diri sebagai agen Islam moderat yang aktif mengajarkan, mengkampanyekan dan meneguhkan moderasi beragama dalam kontestasinya dengan kelompok-kelompok Islam politik radikal. Bagaimanapun, keterlibatan aktif PTKI dalam merespon gerakan radikalisme agama telah berkontribusi penting bagi penguatan modersdalam konteks sosial-politik yang terus berubah.